2012
DOI: 10.3892/or.2012.1982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cellular lethality in DNA repair-proficient or -deficient cell lines resulting from exposure to 70 MeV/n protons or 290 MeV/n carbon ions

Abstract: Charged particle therapy utilizing protons or carbon ions has been rapidly intensifying over recent years. The present study was designed to jointly investigate these two charged particle treatment modalities with respect to modeled anatomical depth-dependent dose and linear energy transfer (LET) deliveries to cells with either normal or compromised DNA repair phenotypes. We compared cellular lethality in response to dose, LET and Bragg peak location for accelerated protons and carbon ions at 70 and 290 MeV/n,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
3
18
1
Order By: Relevance
“…Thus, these highly clustered foci represent a hall mark of high LET radiation. The presence of larger and persistent γH2AX foci after high LET damage and the dependency on NHEJ for repair has been reported previously, although detailed analysis of their complexity has not been hitherto described [5], [18], [19], [21], [33], [34], [35]. Perhaps surprisingly, we also observed some foci clustering following exposure to X-rays although such clustered foci were much smaller, less complex and distinct in nature to that observed after high LET irradiation.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, these highly clustered foci represent a hall mark of high LET radiation. The presence of larger and persistent γH2AX foci after high LET damage and the dependency on NHEJ for repair has been reported previously, although detailed analysis of their complexity has not been hitherto described [5], [18], [19], [21], [33], [34], [35]. Perhaps surprisingly, we also observed some foci clustering following exposure to X-rays although such clustered foci were much smaller, less complex and distinct in nature to that observed after high LET irradiation.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, the biological effect of irradiation with the SOBP beam region of C ions was assessed using the OptiCell™ culture system, as reported previously (10,11), and used to construct a three-dimensional geometric in vitro experiment. The results of the present study demonstrated that a 6 cm wide SOBP C beam consists of various monoenergetic Bragg peak beams, which cause rapid build-up of radiation dosage at a depth of 8 cm, a gradual decrease until the proximal boundary and a rapid decrease at 14 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The cell survival assay using OptiCell culture chambers was performed as described previously (10,11). For the OptiCell survival assay following irradiation with SOBP C ions, 10 ml of culture medium containing between 400 and 600 cells was added to each chamber ~3 h prior to irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature suggests a trend for a higher proton RBE in x-ray–resistant versus x-ray–sensitive cells [2023]. However, in studies using wild-type and DNA-PKcs–deficient or DNA-PKcs–inhibited cells (or other key constituents of NHEJ), a significant proton RBE difference between sensitive and resistant cells has generally not been observed [15, 16, 24, 25]. …”
Section: Introductionmentioning
confidence: 99%